Performance nutrition guidelines for international rugby sevens tournaments - Dziedzic, C. E.; Higham, D. G. (International Journal of Sport Nutrition and Exercise Metabolism, 2014)
Rugby sevens is an abbreviated version of rugby union, played by teams of seven players over 7-min halves. International competitions are usually played in a tournament format. While shorter in duration, the movement demands of rugby sevens per min of match time are greater than rugby union, resulting in an accentuated load on players. This load can be repeated up to six times over a typical 2- or 3-day competition period. The potential cumulative effect of inadequate carbohydrate, protein and/or fluid intake over the course of a tournament is the greatest nutrition-related concern for players. Nutritional strategies before and during competition are suggested to replenish substrate stores, maintain fluid balance and promote recovery between matches. The use of ergogenic aids known to enhance intermittent, high-intensity activity and/or the execution of motor skills may be advantageous to rugby sevens performance and is discussed. This review provides a best-practice model of nutritional support for international rugby sevens competition based on our current understanding of the sport combined with pragmatic guidelines and considerations for the practitioner.